The marketing mix at a free fair (Research, Society and Development, 2021)
For the success of an organization it is necessary to use tools capable of identifying the needs and desires of its target audience. Thus, the objective of this research was to analyze the influence of the Marketing Mix in consumer decision making at an open market. To this end, a field research was carried out at Feira Bela Vista, installed every Friday in the city of Dianópolis / TO. The research methodology is of an applied nature, with a quantitative approach, with its descriptive objectives and field research. The instrument used for data collection was the structured questionnaire, which was applied through the Google forms platform, the sample was composed of 218 respondents. This study highlighted the influences of the marketing mix on consumer decision making and it is clear that the consumer can be influenced by internal and external factors.